PROBLEMATIKA PENERAPAN NEO MABIMS DALAM PENENTUAN AWAL BULAN RAMADAN, SYAWAL DAN DZULHIJJAH 1443 H DI INDONESIA - Hariyono Hari Yono; Nursodik Nursodik (Jurnal Al-Fatih, 2022)
The problem of unification of the Hijri calendar which is still a question mark whether it can be realized, especially in Indonesia because of differences in the method or method in determining the initial change of the Hijri Month. In Indonesia, each Islamic Organization has quite different methods and criteria in determining the beginning of the Hijri Month, such as Nahdlatul Ulama (NU), Muhammadiyyah, Islamic Association (PERSIS), Naqsabandiyah, AnNadzir, Washiliyah and Aboge. So then, this is the result of the emergence of differences in the beginning of fasting Ramadan, fasting Arafah, Eid al-Fitr and Eid al-Adha in Indonesia dragging on until now. Meanwhile, the government as the sole authority has made various efforts to unify the Hijri calendar in Indonesia, namely with the criteria for Neo Visibility Hilal MABIMS (3-6.4) which was just ratified on December 8, 2021. This research is a qualitative research in the form of field research, this type of research is field research, namely research whose object is about the symptoms or events that occur in community groups. However, the fact is that the difference in starting the Lunar month in Indonesia is caused by various factors, namely: Visibility factor, Nash factor, and Political factor.